2015
DOI: 10.1021/acs.macromol.5b01259
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous Evidence for a Highly Mobile Surface Layer in Ultrathin Polymer Films by Specific Heat Spectroscopy on Blends

Abstract: Despite the decade long controversial discussion on the effect of nanometer confinement on the glass transition temperature (T g ) of ultrathin polymer films, there is still no consistent picture. Here, the dynamic calorimetric glass transition of ultrathin films of a blend, which is miscible in the bulk, is directly investigated by specific heat spectroscopy. By a self-assembling process, a nanometer thick surface layer with a higher molecular mobility is formed at the polymer/air interface. By measuring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 49 publications
2
38
1
Order By: Relevance
“…15) and acceleration of equilibrium recovery in the physical aging regime, 16,17 appear at film thicknesses considerably larger than those where alterations of the rate of spontaneous fluctuations are observed. [18][19][20] Such decoupling has been observed measuring simultaneously the rate of spontaneous fluctuations and the thermal T g . [21][22][23][24] Additional indications can be provided by experiments where the same perturbation is applied in the linear and non-linear regimes, for instance in calorimetry where the perturbed magnitude is the entropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) and acceleration of equilibrium recovery in the physical aging regime, 16,17 appear at film thicknesses considerably larger than those where alterations of the rate of spontaneous fluctuations are observed. [18][19][20] Such decoupling has been observed measuring simultaneously the rate of spontaneous fluctuations and the thermal T g . [21][22][23][24] Additional indications can be provided by experiments where the same perturbation is applied in the linear and non-linear regimes, for instance in calorimetry where the perturbed magnitude is the entropy.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In any case, effects on the rate of spontaneous fluctuations in nanostructured polymers are limited to the very first layers close to the interface. [18][19][20] Conversely, deviations of the nonequilibrium dynamics can be visible for length scale of nanostructuring as large as microns, as shown in films 17,[29][30][31][32][33] and polymer nanocomposites. [34][35][36][37] A plausible explanation to the more pronounced effect of reducing film thickness on the nonequilibrium dynamics relies on purely geometric arguments, in particular on the role of "free" interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in glassy polymers, extensive studies have shown the presence of a highly mobile surface layer on the order of tens of nanometers thick. [19][20][21][22][23][24][25][26] In the case of glassy (or amorphous) inorganic materials, whether or not a similar surface layer exists, however, is largely unexplored. A prior study has indicated such a possibility through imaging the motion of surface atoms in ultrathin SiO 2 films 27,28 , but its effect on the dynamic mechanical properties is not known.…”
mentioning
confidence: 99%
“…Nanoscale glassy films are ubiquitous and critical components for a variety of electronic and energy devices such as optical coatings, amorphous oxide transistors , and gate dielectrics, nonvolatile solid state memory, , memristors, solid-electrolyte interphase layers and anodes , in batteries, and amorphous Si solar cells. , The mechanical properties of such amorphous materials are practically important in system design and issues can arise when shrinking them down to nanoscale dimensions. For instance, in glassy polymers, extensive studies have shown the presence of a highly mobile surface layer on the order of tens of nanometers thick. In the case of glassy (or amorphous) inorganic materials, whether or not a similar surface layer exists, however, is largely unexplored. A prior study has indicated such a possibility through imaging the motion of surface atoms in ultrathin SiO 2 films, , but its effect on the dynamic mechanical properties is not known.…”
mentioning
confidence: 99%
“…The procedure of “Guiselin’s experiment” provides the adsorbed layer by annealing and subsequent solvent washing [ 13 ]. Many experiments have shown that the residual adsorbed layer thickness depends on the annealing time at an elevated temperature [ 14 , 15 , 16 , 17 , 18 , 19 ]. Dielectric spectroscopy provided real-time measurements of adsorption kinetics in a buried interface with an aluminum substrate [ 20 ].…”
Section: Introductionmentioning
confidence: 99%